Determination of Political Participation: Money Politics and Voter Political Behavior in the 2020 Batanghari Regional Election - SYUKRI, AHMAD; SARI, INRINOFITA; MAULANA, MUHAMMAD AKBAR; NURFAISAL, MUHAMMAD DWI (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2026)
Political participation is an activity or various voluntary activities of the community to take part in the election process for the ruler. The purpose of this study is to see whether Money Politics and Voter Political Behavior have an influence on the Level of Political Participation in the 2020 Batanghari Regency Election. This study uses a quantitative method with data collection techniques assisted through Google Forms in compiling questionnaires distributed to respondents. This study uses simple random sampling with a population of people who have the right to vote in the 2020 Batanghari Regency Election. This study uses the Slovin formula by taking a sample of 50 respondents. The results of this study indicate that the variables of Giving Money (X1), Giving Goods (X2), and Psychological Approach (X4) have a positive value or have a significant effect on the Level of Political Participation in the 2020 Batanghari Regency Election. Meanwhile, the Sociological Approach variable (X3) has a negative value or does not have a significant effect on the Level of Political Participation in the 2020 Batanghari Regency Election. Furthermore, the interpretation of the regression results and R-Square on the Political Participation Level (TPP) variable is 95%, so the scale obtained is in the strong or good category.